A Simplified Consensus Protocol Simulator With Applications On Proof Of Contribution-X - Peter, Oyinloye Damilare (2023)
Blockchain consensus protocols are the major architectural components of blockchain networks. Numerous enhancements of popular blockchain consensus protocols, such as Proof of Work (PoW) and Proof of Stake (PoS), have led to the emergence of alternative consensus protocols, some of which cater to specific areas such as medicine or transportation. A considerable amount of research has been done on these alternative protocols, one class of which is known as Consensus Protocols Based on Past Behaviour (CPPB). However, these protocols remain relatively unknown and lack performance analysis, which hinders their possible deployment in real-world blockchain networks because the strengths and weaknesses of these consensus protocols cannot be determined. This problem stems from the lack of simulation tools for other consensus protocols that are not mainstream. This gap is bridged by proposing a simple simulation framework called SIM-P, which can accurately simulate the behaviour of these consensus protocols with ease. SIM-P is an agent-based stochastic simulator that relies on the sequential Monte Carlo method to model how block publishers are selected. Simulation models are developed for PoW as a base model for benchmarking purposes, as well as for two selected CPPBs: